Review: Roberts, Simon Gwyn. 2020. From the Welsh Border to the World: Travels in Minority Languages - Hoyte-West, Antony (Studia Celtica Posnaniensia, 2020)
Review: Roberts, Simon Gwyn. 2020. From the Welsh Border to the World: Travels in Minority Languages. Chester: University of Chester Press. 228 pages. ISBN 978-1-908258-37-3. Review by ANTONY HOYTE-WEST, Adam Mickiewicz University in Poznań.